Analisis Experiential Marketing Terhadap Loyalitas Konsumen Alfamart (Studi Kasus Pada Konsumen Alfamart di Kota Pontianak) - B11109120, ARIE RAHADIAN (Jurnal Manajemen Update, 2015)
The Objective of this study was to investigate the influence of Experiential Marketing on customer loyality of Alfamart in Pontianak. This study consisted of dependent variable, namely customer loyality (Y) and five independent variables consisting of Experiential Marketing sense (X1), feel (X2), think (X3), act (X4) and relate (X5). Population of this research was customers of Alfamart with 96 respondents as sample. Sampling technique used was purposive sampling (jugment sampling) and data was analyzed by multiple regression analysis. Findings of test carried out partially and simultaneously indicated that only think and relate significantly influence, while the other independent variable components did not have a significant influence. But the sense, feel, think, act and relate have significant influence in simultaneous test. Based on result of Adjusted R Square, it was acquired a score of 66.4%. This value demonstrated that 33.6% was influenced by other variables outside of this study. Keywords : Experiential Marketing, Customer Loyalty.